AVANSUS Extension Project: Right health, citizenship and its interfaces - Pereira dos Santos, Wallison; Bernardo de Lima, Gigliola Marcos (Guará Journal, 2018)
The University Extension is the great key to the university’s approximation with the local community, in order to contribute to the formation of citi-zenship and dissemination of knowledge. The objective is to present the experience acquired from the experience as a grant holder of the exten-sion project and provide information for the construction of new exten-sion projects in a wide range of fields. It is characterized as a descriptive, qualitative study in the modality of experience reporting, experienced by the scholarship student of the Extension Project "AVANSUS", Federal University of Campina Grande, Campus Cuité-PB. The results were orga-nized into three categories, namely: Construction and application of the board to the community; Experience as a project grantee; Impacts of the AVANSUS project. Through the results obtained in the present study, it is clear that the project reached the proposed objectives and effectively contributed to the rapprochement between the local community and the university.